Reorganization in the human brain as illustrated by the thalamus. - Passingham, R; Heywood, C; Nixon, P (1986)
A comparison is made between the relative size of the various thalamic nuclei in man and other primates. Using data for non-human primates predictions are made as to the expected size of the nuclei for the human brain. Of the nuclear groupings five are of the size predicted but three are not. The lateral geniculate is proportionately smaller than predicted, but it is argued that this need not imply a radical change.